Increased protein intake reduces lean body mass loss during weight loss in athletes - Mettler, S.; Mitchell, N.; Tipton, K. D. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
To examine the influence of dietary protein on lean body mass loss and performance during hypoenergetic weight loss in athletes. Methods: In a parallel design, 20 healthy, young, resistance trained athletes were examined for energy expenditure for one week and fed a fully controlled mixed diet (15% protein, 100% energy) in the second week, followed by a hypoenergetic diet (60% of the habitual energy intake), containing either 15% (~1.0 g x kg-1) protein (control group, n=10) or 35% (~2.3 g x kg-1) protein (high protein group, n=10) for two weeks. Subjects continued their habitual training throughout the study. Total, lean body and fat mass, performance (squat jump, maximal isometric leg extension, one repetition maximum bench press, muscle endurance bench press and 30 sec wingate test) and fasting blood samples (glucose, non esterified fatty acids (NEFA), glycerol, urea, cortisol, free testosterone, free IGF-1 and growth hormone) were examined at the end of each of the four weeks. Results: Total (-3.0 ± 0.4 kg and -1.5 ± 0.3 kg for the control and high protein group, respectively, p=0.036) and lean body mass loss (-1.6 ± 0.3 kg and -0.3 ± 0.3 kg, p=0.006) were significantly larger in the control group compared to the high protein group. Fat loss, performance and most blood parameters were not influenced by the diet. Urea was higher in the high protein group and NEFA and urea showed a group*time interaction. Conclusion: These results indicate that ~2.3 g x kg-1 or ~35% protein was significantly superior to ~1.0 g x kg-1 or ~15% energy protein for maintenance of lean body mass in healthy young athletes during hypoenergetic weight loss.